Effect of Administering Enteral Nutrition pre Caesarean Section Towards High Sensitivity C-Reactive Protein Levels - Rahmadi, Taufik (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To determine the effect of enteral nutrition pre caesarean section (CS) on high sensitivity C-Reactive Protein (hsCRP) serum levels post CS. Method: This clinical trial study on elective CS patients with lumbal anesthesia, was done to compare hsCRP levels two hours pre and 48 hours post CS between the treatment group (P) who was given 200 ml enteral nutrition per oral and control group (K) received 200 ml sweet tea two hours pre CS. The study was already approved by the Ethical Clearance Research Committee of Faculty of Medicine University of Indonesia. Results: Twenty seven elective CS patients in Rumah Sakit Umum Daerah (RSUD) Bekasi were selected using certain criteria and divided into two groups using block randomization. Data collected included age, gestational age, nutritional status, indication, of CS total blood volume, and duration of CS, as well as energy intake of energy and protein. Laboratory hsCRP serum levels were examined two hours pre and 48 hours post CS. Statistical analysis were performed using t-test and Mann-Whitney, with 5% level of significancy. Twelve subjects in each P and K group, completed the study respectively. The mean of age was 30.08 Â± 4.01 years. The nutritional status based on upper mid arm circumference in both groups was normal, while using kartu menuju sehat (KMS) in all of subjects were classified as overweight. The characteristic of the two groups closely matched at base line (p > 0.05). There was increased hsCRP serum at post CS which was higher in the K group and statistically significant (p = 0.00). Conclusion: Administration of 200 ml enteral nutrition two hours pre CS is associated with a reduction of 48 hours post CS hsCRP serum level compared with sweet tea. [Indones J Obstet Gynecol 2010; 34-4: 159-63] Keywords: elective CS, enteral nutrition pre CS, hsCRP serum concentration